2020
DOI: 10.1136/bmjopen-2020-039692
|View full text |Cite
|
Sign up to set email alerts
|

‘There were some clues’: a qualitative study of heuristics used by parents of adolescents to make credibility judgements of online health news articles citing research

Abstract: ObjectiveTo identify how parents judge the credibility of online health news stories with links to scientific research.DesignThis qualitative study interviewed parents who read online stories about e-cigarettes and human papillomavirus (HPV) vaccination published by top-tier US news organisations. Researchers asked participants to describe elements of a story that influenced their judgement about content credibility. Researchers analysed transcripts using inductive and deductive techniques. Deductive analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…All participants mentioned exposure to misleading health information on social media even when they were not actively using it. Distrust in social media as a source of health information was exhibited through descriptions of “algorithmic bias,” “persuasive intent,” and “financial motives,” which in turn created “polarization” and “echo chambers.” These social phenomena were also linked to cognitive heuristics applied by individuals to (1) ensure credibility of information sources through the “reputation” heuristic and (2) limit misinformation exposure through the “self-confirmation” heuristic, and they are aligned with existing literature [ 42 ].…”
Section: Resultsmentioning
confidence: 84%
“…All participants mentioned exposure to misleading health information on social media even when they were not actively using it. Distrust in social media as a source of health information was exhibited through descriptions of “algorithmic bias,” “persuasive intent,” and “financial motives,” which in turn created “polarization” and “echo chambers.” These social phenomena were also linked to cognitive heuristics applied by individuals to (1) ensure credibility of information sources through the “reputation” heuristic and (2) limit misinformation exposure through the “self-confirmation” heuristic, and they are aligned with existing literature [ 42 ].…”
Section: Resultsmentioning
confidence: 84%
“…FGD and interview data were transcribed and analyzed thematically [ 70 ] using Microsoft Excel. Through a heuristic process [ 66 , 71 ], multiple rounds of going through the transcribed data and field notes permitted the identification of phrases linked to the originally established question codes. These were then arranged into themes in accordance with question codes by means of cut and paste.…”
Section: Methodsmentioning
confidence: 99%
“…Banning and Sweetser, 2007;Hargittai, et al, 2010;Metzger, et al, 2010;Pan, et al, 2007). Individuals have been found to use these heuristics to assess specifically online health information (Rieh, 2014), including that gained via health apps (Kanthawala, et al, 2019) and news sources (Maggio, et al, 2020). One study found that users rely heavily on multiple complementary heuristics to evaluate the credibility of online health information rather than employ intensive systematic processing of information (Klawitter and Harittai, 2018b).…”
Section: The Role Of Heuristicsmentioning
confidence: 99%